Formulasi, Karakterisasi, Dan Evaluasi Drops Liquid Self Nano-Emulsifying Drug Delivery System (SNEDDS) Astaxanthin - Robert Tungadi; Nur Ain Thomas; Wanda Gita Van Gobel (Jurusan Farmasi Universitas Negeri Gorontalo, 2021)
SNEDDS are isotropic mixtures of oil, surfactant, and cosurfactant that produce spontaneous nanoemulsions once they make contact with gastric juices in order to increase the solubility of active pharmaceutical ingredients. One of the active pharmaceutical ingredients with low solubility is Astaxanthin. This research aims at formulating, characterizing, and evaluating SNEDDS containing Astaxanthin in the form of droplets. This research is a laboratory experiment. SNEDDS containing Astaxanthin droplets are made in 3 formulas using the ratio of surfactants and co-surfactants which are characterized to produce F1, F2, and F3 transmittance values of 91%, 90%, and 95%, respectively. Furthermore, the F1 particle size value of 183.75 nm obtains a PDI value of 0.272, the F2 particle sizevalue of 195.25 nm obtains a PDI value of 0.341, and the F3 particle size value of 105.75 nm obtains a PDI value of 0.392. This signifies that the absorption efficiency of F1, F2, and F3 are 94.62%, 94.35%, and 95.57%, respectively. The evaluation reveals the insignificant changes in the emulsion viscosities of SNEDDS containing Astaxanthin liquid drop after having received a stability test for 28 days using Paired T. Test data analysis (p0.05). The research findings show that the F3 of 72% surfactant and 18% co-surfactant concentrations are the best formula in producing SNEDDS. It concludes thar the higher the surfactant concentration produced, the greater the ability to, oil droplets resulting in obtaining small partidles and high absorption efficiency.